Screening for Fusarium Antagonistic Bacteria From Contrasting Niches Designated the Endophyte Bacillus halotolerans as Plant Warden Against Fusarium - Slama, Houda Ben; Cherif-Silini, Hafsa; Chenari Bouket, Ali; Qader, Mallique; Silini, Allaoua; Yahiaoui, Bilal; Alenezi, Faizah N.; Luptakova, Lenka; Triki, Mohamed Ali; Vallat, Armelle; Oszako, Tomasz; Rateb, Mostafa E.; et al. (Frontiers in Microbiology, 2019)
Date palm (Phoenix dactylifera L.) plantations in North Africa are nowadays threatened with the spread of the Bayoud disease caused by Fusarium oxysporum f. sp. albedinis that already wiped out dates production in infected areas mainly in Morocco. Biological control holds great promise for sustainable and environmental-friendly management of the disease. In this study, using plant growth promoting rhizobacteria (PGPR) or endophytes additional benefits to agricultural ecosystems are addressed. First, PGPR or endophytes can offer an interesting bio-fertilization mean that can add another layer to the sustainability of the approach. Additionally, screening of contrasting niches can yield bacterial actors that could represent wardens against whole genera or groups of plant pathogenic agents thriving in the semi-arid to arid ecosystems. Using this strategy, we recovered four bacterial isolates designated BFOA1, BFOA2, BFOA3 and BFOA4 that proved very active against Fusarium oxysporum f. sp. albedinis. BFOA1–BFOA4 proved also active against 16 Fusarium isolates belonging to three species Fusarium oxysporum (with strains phytopathogenic of Olea europeae and tomato), Fusarium solani (with different strains attacking Olea europaea and potato), Fusarium acuminatum (pathogenic on Olea europeae) and Fusarium chlamydosporum phytopathogenic of Olea europeae). BFOA1-BFOA4 bacterial isolates exhibited strong activities against another four major phytopathogens Botrytis cinerea, Alternaria alternata, Phytophthora infestans and Rhizoctonia bataticola. Isolates BFOA1–BFOA4 had the ability to grow at temperatures up to 35 °C, pH range of 5–10, and tolerate high concentrations of NaCl and up to 30% PEG. The isolates also showed relevant direct and indirect PGP features including growth on nitrogen-free medium, phosphate solubilization and auxin biosynthesis, as well as resistance to metal and xenobiotic stress. Phylogenomic analysis of BFOA1–BFOA4 isolates indicated that they all belong to Bacillus halotolerans that could therefore considered as warden against Fusarium infection in plants. Comparative genomics allowed to functionally describe the open pan genome of B. halotolerans and LC-HRMS and GCMS analyses allowed the description of diverse secondary metabolites including: pulegone, 2-undecanone and germacrene D with important antimicrobial and insecticidal properties. In conclusion, B. halotolerans could be used as efficient bio-fertilizer and bio-control agent in semi-arid and arid ecosystems.